Analysis of Household Expenditure Structure and Determinants of Household Expenditure Among Aquaculture Workers In Cindai Alus Village, Martapura District, Banjar Regency - Noor Rachmat Sandiko; Emmy Lilimantik; Erma Agusliani (International Journal of Science and Environment (IJSE), 2026)
In recent years, Islamic banks in Indonesia have experienced rapid Growth, especially in the province of Aceh. Even though the Growth of Islamic banks is quite rapid, as seen in data from the Financial Services Authority (OJK), their market share in Indonesia is still far below that of conventional banks. The Third-Parties Fund at Bank Aceh Syariah is interesting to study as a measure of how the Bank can attract customers to save with it through Return on Assets (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR). The population of this study is the Bank Aceh Syariah. The data collection technique used the documentation method on the official banking website of Bank Aceh Syariah. The methodology of this research is quantitative. The data used are secondary, obtained from Bank Aceh Syariah's annual reports from 2011 to 2020. In this study, the data analysis included descriptive analysis, validity tests, pilot tests, reliability tests, and classic assumption tests. And for hypothesis testing, multiple regression, adjusted R2, F-statistic, partial test (T-test), and automatic linear modeling are used. The data is processed using SPPS for Windows.